Risk and Crisis Management in the Public Sector - Drennan, Lynn T., 1953-; Dudau, Adina; McConnell, Allan; Stark, Alastair (Masters in public management, 2024)
"Risk and Crisis Management in the Public Sector 3rd edition is a guide for public managers and public management students which combines practical and scholarly knowledge about risk and crisis management together in a single accessible text. In the uncertainty of the twenty-first century, public managers need to know how to identify risks and plan for crises, how to respond to uncertain events and emergencies, and how to develop resilience . This book provides this fundamental knowledge with reference to a range of contemporary cases including Covid-19, the war in Ukraine and global cyber-crime crises. It also explores the international, trans-boundary and multi-agency dimensions of risk and crisis management. This fully updated new edition explores the cutting edge of risk and crisis management scholarship, provides an extensive series of tools and practical guidance for public managers who deal with uncertainty and draws on a wealth of classic and contemporary case studies. This content equips readers and public managers with the knowledge and skills to understand key issues and debates, as well as the capacity to treat risks and better prepare for, respond to and recover from crisis episodes. This book is essential reading for students studying public management, risk management and crisis management as well as professionals in the public management sector"--